What factors drive change in management accounting in Malaysian organisations? / Suzana Sulaiman, Aliza Ramli and Falconer Mitchell - Sulaiman, Suzana (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
Without knowledge of how the management accounting (MA) discipline changes, its development cannot be properly understood. Prior research indicates that MA has been changing and that many factors are implicated in its change. This study explores the factors which cause management accounting change in Malaysia. MA change is taken to encompass not only MA per se but also its composition as represented by the techniques, skills and roles of the management accountant. These are investigated by surveying experienced, professionally qualified management accountants working in Malaysian organisations. A range of factors were identified as significant change drivers and these differ across the three components of MA.